Pengaruh video edukasi interaktif terhadap peningkatan pengetahuan ibu hamil tentang ASI Eksklusif - Andi Tenri Wika; Andi Asrina; Nur Ulmy Mahmud; Yusriani Yusriani; Fairus Prihatin Idris; Sumiaty Sumiaty (An Idea Health Journal, 2026)
Background: This Study aimed to evaluate the effect of educational video interventions on improving pregnant women's knowledge regerding exclusive breastfeeding using two comparison groups. although digital learning media have become widely implemented in maternal health promotion, passive video delivery often limits comprehension and learning retention. intergrating interaction within digital education may enhance understanding by enabling clarification and strengthening information processing. A quasi- xperimental pretest-posttest design was conducted involving 34 pregnant women divided into two groups: an intervantion group receiving educational video with interactive discussion (n=17) and a comparison group receiving the same video without interaction (n=17). knowlegde was measured before and after the intervention and analyzed using the wilcoxon signed rank test and Mann- whitney U test. result showed that both groups experienced increases in posttest knowledge scores; however, improvement was greater in the interaction group. The Wilcoxon analysis demonstrated significant knowledge gains in the interactive group ( Z =-3.643 ; p = 0.000). Meanwhile, Mann-Whitney analysis indicated that the knowledge improvement between the two groups was significantly different, favoring the interaction approach. These findings demonstrate thet educational videos accompanied by interaction are more effective in improving maternal knowledge compared to passive video delivery. Strengthening interaction-based digital health education is recommended to support maternal and child health programs.